Evaluating Governance Arrangements and Decision Making for Natural Resource Management Planning: An Empirical Application of the Governance Systems Analysis Framework. Issue 11 (1st November 2016) - Potts, Ruth; Vella, Karen; Dale, Allan; Sipe, Neil
ABSTRACT: Governance continues to be a challenge in the management and conservation of natural resources. It is difficult to strategically address governance challenges without understanding the dynamics, capacities, and knowledge application of institutions within such governance systems. This article examines the use of Governance Systems Analysis (GSA) to compare, evaluate, and benchmark governance arrangements for regional natural resource management (NRM) planning. It is applied in two Australian regional NRM case studies in Cape York and the Wet Tropics. Our analysis of governance arrangements for NRM planning in the two regions finds that while they are structurally and functionally similar, they have different capacities for decision making about planning. The article concludes with a discussion of the usefulness and implications of using the GSA as an evaluative framework to analyze governance in regional NRM planning systems.